Slowly progressive Lemierre's syndrome with orbital pain and exophthalmos. Issue 1 (January 2016) - Hama, Yuka; Koga, Masatoshi; Fujinami, Jun; Asayama, Shinya; Toyoda, Kazunori
Abstract: Lemierre's syndrome is an oropharyngeal bacterial infection characterized by rapidly progressive septic thrombophlebitis of the internal jugular vein. A lack of appropriate antibiotic therapy can be life-threatening. We describe the case of a 39-year-old man with Lemierre's syndrome who presented with long-lasting orbital pain and acute exophthalmos 6 weeks after initial infection. This report is to help clinicians consider the diagnosis of Lemierre's syndrome when encountering a patient with long-lasting orbital pain and acute exophthalmos. Neck ultrasonography is useful for detecting thrombophlebitis of the internal jugular vein in Lemierre's syndrome patients.